2021
DOI: 10.1111/cas.15108
|View full text |Cite
|
Sign up to set email alerts
|

WEE1 inhibitor and ataxia telangiectasia and RAD3‐related inhibitor trigger stimulator of interferon gene‐dependent immune response and enhance tumor treatment efficacy through programmed death‐ligand 1 blockade

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Accordingly, Wee1 inhibition reconstitutes CDK1 activity to reverse resistance of these cancer cells to immune attack ( 194 ). In various cancer models, Wee1 inhibition promotes accumulation of cytosolic dsDNA, leading to activation of the cGAS-STING pathway ( Figure 1 ), increased type I interferon target gene expression when delivered alone ( 195 ), as well as in combination with ATR inhibitors ( 196 ) or immune checkpoint blockade ( 197 ). A STING-independent pathway by which Wee1 inhibition induces the interferon response has also been reported.…”
Section: Targeting the Dna-damage Response Pathwaymentioning
confidence: 99%
“…Accordingly, Wee1 inhibition reconstitutes CDK1 activity to reverse resistance of these cancer cells to immune attack ( 194 ). In various cancer models, Wee1 inhibition promotes accumulation of cytosolic dsDNA, leading to activation of the cGAS-STING pathway ( Figure 1 ), increased type I interferon target gene expression when delivered alone ( 195 ), as well as in combination with ATR inhibitors ( 196 ) or immune checkpoint blockade ( 197 ). A STING-independent pathway by which Wee1 inhibition induces the interferon response has also been reported.…”
Section: Targeting the Dna-damage Response Pathwaymentioning
confidence: 99%
“…Recent preclincal studies show that ATRi increases type I interferon (IFN) signaling and production of proinflammatory cytokines and chemokines after radiation in vitro and in vivo (19,26). Similar proinflammatory signaling occurs after DNA damage induced by combined ATR and WEE1 inhibition (28). Furthermore, combined ATRi and radiotherapy is associated with increased antigen presentation on tumor cells and myeloid immune cell infiltration of tumors in vivo (19).…”
Section: Short-course Atri Treatment Potentiates Radiotherapy-induced...mentioning
confidence: 99%
“…In these clinical investigations, ATR kinase inhibitors are being combined with genotoxic chemotherapy, poly (ADP-ribose) polymerase (PARP) inhibitors, radiotherapy, and immunotherapy, and substantial preclinical evidence demonstrates that AZD6738 (ATRi) sensitizes cells to DNA damaging agents (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). More recently, preclinical studies have also shown that ATRi can potentiate anti-tumor immune responses, but the underlying mechanisms are not well-understood (17,19,(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with different ATRi results in innate immune and T cell activation mediated by cGAS-STING pathway in various mouse models of cancer, including those for prostate cancer [ 60 ], hepatocellular carcinoma [ 34 ] and ovarian cancer [ 61 ]. The combination of a WEE1i (adavosertib) and an ATRi (ceralasertib) also promotes accumulation of cytosolic dsDNA, which subsequently activates the STING pathway and induces the production of type I IFN and the recruitment and activation of CD8 T cells—thereby inducing antitumour immunity [ 62 ]. Similar induction of antitumour immunity through STING activation has been reported after treatment with ATMi [ 63 , 64 ].…”
Section: Ddr-targeted Agents Modulate Pathways In Tumour Cells That Impact Their Relationships With Immune Cellsmentioning
confidence: 99%
“…PD-L1 is also upregulated by other DDR-targeted agents besides PARPi. For instance, upregulation of PD-L1 was observed after the combination of a WEE1i (adavosertib) and an ATRi (ceralasertib) [ 62 ]. Although PD-L2 may also play a similar role as PD-L1, the effects of DDR-targeted agents on PD-L2 expression have not been explored so far.…”
Section: Ddr-targeted Agents Modulate Pathways In Tumour Cells That Impact Their Relationships With Immune Cellsmentioning
confidence: 99%